[LB.02.04] EFFECTS OF RENAL DENERVATION IN PATIENTS WITH VERSUS WITHOUT CHRONIC KIDNEY DISEASE: RESULTS FROM THE GLOBAL SYMPLICITY REGISTRY WITH FOLLOW-UP DATA OF 3 YEARS. (September 2017) - Ott, C.; Mahfoud, F.; Mancia, G.; Narkiewicz, K.; Ruilope, L.M.; Schlaich, M.P.; Williams, B.; Böhm, M.; Schmieder, R.E.
Abstract : Objective: Activity of the sympathetic nervous system (SNS) is increased in hypertensive patients with chronic kidney disease (CKD). We tested the hypothesis that hypertensive patients with CKD enrolled in the Global Symplicity Registry (GSR) show different patterns in blood pressure (BP) outcomes in the short-term (6 months), as well as long-term follow-up (3 years). Design and method: The GSR (NCT 01534299) is a prospective, open-label, international, multicentre observational study for assessment of safety and effectiveness of renal denervation (RDN) among real-world patients treated with the Symplicity™ RDN system (Medtronic, Santa Rosa, CA, USA). Inclusion criteria are age > = 18 years and eligibility for RDN. 24-h ambulatory BP was assessed at pre-specified time-points (6, 12, 24 and 36 months). For the current analyses, enrolled patients (N = 1600) were stratified based on baseline estimated glomerular filtration rate (eGFR) in <60 ml/min/1.73 m 2 versus > = 60 ml/min/1.73 m 2 (according to MDRD formula) into with (N = 383) and without (N = 1217) CKD groups. Results: Patients with CKD were significantly older (65.3 ± 11 versus 59.9 ± 12 yrs, p < 0.0001) and were treated with more antihypertensive medications (4.78 ± 1.3 versus 4.48 ± 1.4, p < 0.0001) compared to patients without CKD. There was no difference in baseline 24-h ambulatory systolic BP, whereas 24-h ambulatory diastolic BP was lower in patients with compared to without CKD (152.9 ± 19/81.3 ± 13 versus 153.2 ± 18/87.2 ± 14 mmHg, p = 0.6380/ < 0.0001), resulting in an increased pulse pressure. In patients with and without CKD, 24-h ambulatory BP was significantly reduced after RDN compared to baseline values at all time-points (all p < 0.01). There was no difference in 24-h ambulatory systolic and diastolic BP reduction after RDN in favor of patients with compared to without CKD (Table). Figure. No caption available. Conclusions: Hypertensive patients with CKD did not show a greater short-term or long-term decrease in 24-hour ambulatory BP. Changes in pulse pressure and eGFR over the 3 years follow-up will be also presented.